ELABORASI STRATEGI PEMBELAJARAN INDEX CARD MATCH PADA MATA PELAJARAN BAHASA INDONESIA DI MI/SD - Dirga Ayu Lestari (Jurnal Anak Bangsa, 2022)
Elaboration in a learning strategy is one of the efforts to develop an Indonesian language learning scenario for fourth grade MI/SD students which aims to actualize students in four aspects of the Indonesian language, namely reading, listening, writing and speaking in terms of delivering meaningful messages. This research method uses library research so that the method used in the research is library research. The index card match learning strategy is a learning strategy that requires students to work together and can increase students' sense of responsibility for what they learn in a fun way. Students will work together to complete a mission given to them. This group learning activity can trigger active learning and the ability to teach through small group learning activities that allow for understanding and mastery of the material. The elaboration of the index card match (ICM) learning strategy can improve reading, listening, writing and speaking Indonesian MI/SD subjects. This certainly can contribute to the process of developing the four language and literary skills of students, especially MI/SD children which will trigger all aspects of the cognitive, affective and psychomotor domains of students to be better so that the objectives of learning Indonesian language can be achieved. The use of ICM requires a scenario that can develop the social and emotional aspects of students that are synergized in the abilities of MI/SD students who are still in the concrete operational stage with the help of tools in the form of picture cards that must be matched with the description of the children's story given by the teacher